La norma e la libertà: la sfida etica di Paul Ricoeur (Itinera, 2015)
This paper deals with the relation between freedom and norm in the practical philosophy of Paul Ricoeur, taking into account especially the “Little Ethics” that covers Studies VII, VIII, IX of Oneself as Another. Although Ricoeur states the priority of ethics over moral, playing the quest for good and happiness off against deontological morality of duty, it soon appears clear that the norm is necessarily implied by the development of ethics itself. No actual freedom can exist without norm; but, on the other and, no normative system is absolute, because the quest for good, in which freedom consists, cannot be fulfilled by any norm. This is the reason why it is always possible, and in some cases necessary, to act not following the established rules, but by improvisational conducts that can answer to the needs of the given situations. Aim of the article is to show the relevance of creativity for Ricoeur’s theory of action, but also to highlight the fact that creativity is not grounded on itself, but is linked to an infinite ethical ambition that give sense to improvisation.